2009
DOI: 10.5367/000000009789711891
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Higher Education and Industry in Supporting Career Goals and Decision Making

Abstract: Both higher education institutions and employers need to evaluate the factors that influence students' career goals and career-related decisions because of their importance to and impact on career management and decision making. The objective of this study is to identify the importance of career goals and factors influencing students' career decision making in South Africa. A non-probability sample was selected, with 488 completed responses. The findings indicate that there are significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Previous studies demonstrated a pattern of bifurcating the factors influencing graduate job choice in three themes: internal, external and interpersonal factors (Abbasi and Sarwat, 2014;Agarwala, 2008;Albugamy, 2014;Aycan and Fikret-Pasa, 2003;Ng et al, 2008;Fabea, 2014;Gokuladas, 2010;Jordaan, 2009;Lightbody et al, 1997;Omar et al, 2015;Özbilgin et al, 2005;Sultana and Mahmud, 2020;Thampoe, 2016;Wilkinson, 1996). We believe that two more themes, namely, institutional factors (Albugamy, 2014;Fabea, 2014;Gokuladas, 2010;Jordaan, 2009;Lightbody et al, 1997;Omar et al, 2015;Wilkinson, 1996) and sociodemographic factors (Agarwala, 2008;Albugamy, 2014;Ng et al, 2008;Gokuladas, 2010;Jordaan, 2009;Özbilgin et al, 2005;Sultana and Mahmud, 2020;Wilkinson, 1996), are required to be added for better understanding of career choice antecedents more precisely.…”
Section: Proposed Theoretical Modelmentioning
confidence: 76%
See 4 more Smart Citations
“…Previous studies demonstrated a pattern of bifurcating the factors influencing graduate job choice in three themes: internal, external and interpersonal factors (Abbasi and Sarwat, 2014;Agarwala, 2008;Albugamy, 2014;Aycan and Fikret-Pasa, 2003;Ng et al, 2008;Fabea, 2014;Gokuladas, 2010;Jordaan, 2009;Lightbody et al, 1997;Omar et al, 2015;Özbilgin et al, 2005;Sultana and Mahmud, 2020;Thampoe, 2016;Wilkinson, 1996). We believe that two more themes, namely, institutional factors (Albugamy, 2014;Fabea, 2014;Gokuladas, 2010;Jordaan, 2009;Lightbody et al, 1997;Omar et al, 2015;Wilkinson, 1996) and sociodemographic factors (Agarwala, 2008;Albugamy, 2014;Ng et al, 2008;Gokuladas, 2010;Jordaan, 2009;Özbilgin et al, 2005;Sultana and Mahmud, 2020;Wilkinson, 1996), are required to be added for better understanding of career choice antecedents more precisely.…”
Section: Proposed Theoretical Modelmentioning
confidence: 76%
“…Personal interests. Personal interests refer to individual subject items in their life, being one of the variables of an internal factor, has been proposed as a primary determinant of career choice (Gokuladas, 2010;Jordaan, 2009;Sultana and Mahmud, 2020). Students' perception about their skill, competence and ability has been considered as a critical factor for selecting a right career option over another (Agarwala, 2008;Ng et al, 2008;Jordaan, 2009;Özbilgin et al, 2005).…”
Section: Proposed Theoretical Modelmentioning
confidence: 99%
See 3 more Smart Citations